Evaluasi Peningkatan Pengetahuan tentang Menopause melalui Edukasi Kesehatan Reproduksi pada Komunitas Wanita Manjah Squads di Tangerang - Fadhil, Muhammad; Sari, Bunga Anggreini; Sukrisno, Adi; Razi, Fakhri (Jurnal Pelayanan dan Pengabdian Masyarakat (Pamas), 2026)
This community service activity aimed to evaluate the effectiveness of an educational program in improving knowledge about menopause among adult women. The background was based on findings that the majority of women feel unprepared to face the menopausal transition due to significant knowledge gaps. The method employed was a single educational intervention in the form of a seminar, followed by knowledge assessment through pre-test and post-test. The participants consisted of nine women aged 35–54 years from the "Manjah Squads" community in Tangerang. The pre-test results indicated basic understanding but revealed gaps in knowledge regarding non-physical symptoms, long-term health risks, and appropriate management. Descriptive analysis of the two participants who completed the post-test demonstrated holistic improvement in knowledge, encompassing understanding of perimenopause, genetic factors, psychological symptoms, risks of osteoporosis and cardiovascular disease, as well as management strategies such as calcium and vitamin D requirements and basic comprehension of hormone therapy. These findings are consistent with the literature, which suggests that structured education can enhance health literacy, knowledge, and self-efficacy. It is concluded that a brief group education program proved effective in improving menopause-related understanding. It is recommended to conduct continuous education, design more rigorous evaluations, and disseminate this intervention model to other communities